Remembering and forgetting Confederate monuments: taking the bitter with the sweet. (1st March 2022) - Boldrick, Stacy; Clay, Richard; Duster, Michelle; Magee, Keith
Abstract : This article addresses contemporary and long-standing debates over Confederate monuments in the United States by examining the removal of two monuments in Memphis, Tennessee, one dedicated to Nathan Bedford Forrest (1821–77), and the other to Jefferson Davis (1808–89). A review of the rationales behind the origins of the Memphis monuments as objects of commemoration and the longer histories of their sites reveals the troubled nature of these symbols of white supremacy in the events leading to their eventual removal in 2017. It references the alignment of their production with two spikes in Confederate monument production between 1896 and 1919 and 1954 and 1968, during periods of segregation and political nostalgia. The study of the Memphis monuments and the fragility of their historic narratives segues into broader discussions around the analysis of Confederate monuments to propose that although forgetting may lie behind their longevity, remembering is critical to their future interpretation. Such discussions resonate beyond the subject of Southern US Confederate monuments, as part of wider international debates around contested monuments and responses to them.